2021
DOI: 10.3389/fpsyg.2021.794038
|View full text |Cite
|
Sign up to set email alerts
|

Association of Inventory to Measure and Assess imaGe Disturbance – Head and Neck Scores With Clinically Meaningful Body Image-Related Distress Among Head and Neck Cancer Survivors

Abstract: Objective: The Inventory to Measure and Assess imaGe disturbance – Head and Neck (IMAGE-HN) is a validated patient-reported outcome measure of head and neck cancer-related body image-related distress (BID). However, the IMAGE-HN score corresponding to clinically relevant BID is unknown. The study objective is to determine the IMAGE-HN cutoff score that identifies head and neck cancer patients with clinically relevant BID.Methods: We conducted a cross-sectional study at six academic medical centers. Individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Emerging data since this trial was designed have determined that an IMAGE-HN score of 22 or higher indicates clinically relevant HNC-related BID and confirmed that IMAGE-HN is a more sensitive and accurate measure of BID among HNC survivors than the Body Image Scale. 3…”
Section: Study Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging data since this trial was designed have determined that an IMAGE-HN score of 22 or higher indicates clinically relevant HNC-related BID and confirmed that IMAGE-HN is a more sensitive and accurate measure of BID among HNC survivors than the Body Image Scale. 3…”
Section: Study Measuresmentioning
confidence: 99%
“…1 Because these changes are highly visible and affect daily social function, 75% of HNC survivors express body image concerns, 2 and up to 28% have clinically significant body image distress (BID). 3,4 Body image distress is a source of devastating psychosocial morbidity and functional impairment for HNC survivors, contributing to a 6-fold increase in moderate-severe depressive symptoms, an 8-fold increase in moderate-severe anxiety symptoms, as well as social isolation and feelings of stigmatization. 3,[5][6][7][8][9][10] Although clinically significant HNC-related BID does not improve over time without treatment, 11 evidence-based management strategies to manage BID in this population are lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The IMAGE-HN has been shown to be reliable and valid [47 ▪▪ ,49]. It represents a significance advance in the field, and an important tool for evaluating the psychosocial impact of head and neck cancer treatment [49].…”
Section: Screening For Emotional Distress Through Patient-reported Ou...mentioning
confidence: 99%
“…Body image-related distress is a disorder characterized by a distressing self-perceived change in appearance and function [44,45]. It can lead to social isolation, stigmatization, depression, and self-harm [26,46] [49].…”
Section: The Inventory To Measure and Assess Image Disturbance -Head ...mentioning
confidence: 99%